Analysis of rural women preferences for cooking energy in Ikole Ekiti Local Government Area in Ekiti State, Nigeria - Matthew Olufemi Adio; Olarewaju Ayodele; Damilare Ifeoluwa Olufemi; Akindele James Akintola; Abiola Adebunmi Olarinre; Richard Kimbowa; Ahmed-Nor Mohamed Abdi (Discover Sustainability, 2025)
Abstract This research investigated preference for cooking energy among rural women in Ikole Local Government Area (LGA), Ekiti State, Nigeria. In particular, the study outlined the socio-economic traits of rural women, recognized various cooking energy types and estimates factors influencing rural women preference for cooking energy. For the study, a multistage sample approach was employed to choose 105 rural women. Multinomial regression and descriptive statistics were the analytical methods employed. The findings indicated that the average age of the respondents who used purely firewood, firewood in addition to charcoal, firewood plus gas, and purely gas were 47, 42, 40, and 38 years old with mean household size of 5, 5, 4, and 4 members and mean cooking experience of 21, 17, 20, and 20 years respectively. When firewood usage is taken as the base outcome, the multinomial logistic regression result shows that age (0.176, p < 0.1), experience (− 0.129, p < 0.05) were significant variables that determines the preference of charcoal and firewood, education (0.184, p < 0.05), and association (1.529, p < 0.1) were significant variables that determines the preference of firewood and gas, while education (0.495, p < 0.01) and income (4.002, p < 0.05) were significant variables that determines the preference of gas. Conclusively, older women are more inclined to use traditional fuels. Targeted assistance (even if subsidy of any sort) for rural women be put in place to reduce the cost of renewable energy options and enhance their affordability for rural households. Therefore, promoting adoption of sustainable cooking energy solutions also requires on-going education through training and extension services.